Prevalence of Post-traumatic Stress Disorder in Medical Students - Osama Habib, Munaza Javed, Khalid Mahmood, Muhammad Atif Qureshi, Nauman Ismat Butt, Fahmina Ashfaq (Pakistan Journal of Medical & Health Sciences, 2022)
Objective and background: Previous studies have reported a high prevalence of depressive and anxiety disorders in medical students. The aim of the current study was to investigate the prevalence of PTSD symptoms among 1st to 3rd year MBBS students. Place and duration: The study was conducted at Azra Naheed Medical College, Superior University, Lahore, Pakistan from 15th of August o 15th of September 2022. Methodology: A Google form was developed by authors of the study that comprised demographic questions as well as items of post-traumatic stress disorder checklist-Civilian version (PCL-C). The form was posted in the official WhatsApp group of each class and the rationale and purpose of the study were communicated to students. Confidentiality of the data was ensured and anonymity of the participants maintained at all stages. The study was formally approved by the Institutional review board of Azra Naheed Medical College, Lahore. Descriptive statistics, independent samples T-test and the ANOVA test were employed to analyze and report the findings. SPSS version 26 was used for reporting and analyzing the data. Results: A total of 223 medical students (45.4% males) participated in the study. Nearly three quarters of medical students (73.4%) had either moderate, (29.1%) or severe (44.3%) PTSD symptoms. No significant difference was found between the students with regards to gender, age group and year of study. Students who belonged to a mixed rural/urban background had significantly higher PTSD symptoms as compared to students from a predominantly rural or urban background. Practical Implication Medical students should be routinely assessed for the presence of anxiety/depressive disorders, as successful treatment of these disorders may improve the quality of life as well as the academic performance of the students. Conclusions: The prevalence of PTSD symptoms in medical students participating in this study is very high. Future studies should investigate the reasons as well as the risk factors associated with PTSD in medical students. Keywords: Post Traumatic stress disorder, Medical students, Anxiety